2016
DOI: 10.1016/j.seizure.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Risks of probable SUDEP among people with convulsive epilepsy in rural West China

Abstract: Lack of seizure freedom before and during regular antiepileptic drug treatment increase the risk of probable SUDEP. Special attention should be given to patients with early convulsive epilepsy-onset, and the proper control of convulsive seizures is critical for the prevention of probable SUDEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Our analysis supported the importance of several risk factors related to SUDEP. Those present in all our cases were early onset of epilepsy (average, 19.4 years old), poor seizure control, generalized tonic-clonic seizures (GTCS) (0.5-3 per month), poor adherence to treatment, and long-lasting epilepsy (average 16.6 years), in accordance with previous studies [7,[22][23][24][25][26]. The average age at the time of death was 36 years, reinforcing the concept that SUDEP affects mainly young patients [15,27].…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis supported the importance of several risk factors related to SUDEP. Those present in all our cases were early onset of epilepsy (average, 19.4 years old), poor seizure control, generalized tonic-clonic seizures (GTCS) (0.5-3 per month), poor adherence to treatment, and long-lasting epilepsy (average 16.6 years), in accordance with previous studies [7,[22][23][24][25][26]. The average age at the time of death was 36 years, reinforcing the concept that SUDEP affects mainly young patients [15,27].…”
Section: Discussionsupporting
confidence: 90%
“…SUDEP may, kill over 20000 people with epilepsy yearly in China based on the incidence and the huge number of people with epilepsy. Risk factors for probable SUDEP identified were childhood onset of epilepsy, high seizure frequency, and uncontrolled seizures 23 . A whole exome sequencing in samples from incident cases of SUDEP found rare variants in SCN5A, KIF6, and TBX18 genes that support the hypothesis that underlying heart disorder may be a driver of SUDEP risk 24 .…”
Section: Prevalence Incidence and Mortalitymentioning
confidence: 99%
“…However, it could be explained by the matching of initial seizure frequencies, which were not covered by those earlier studies. In addition, one of our previous reports [12] with a different design compared the seizure frequency of the SUDEP group, proving tonic-clonic seizures were more frequent in that group than in other epilepsy patients. Other than a general comparison, this study focused on more specific time periods before SUDEP.…”
Section: Discussionmentioning
confidence: 91%
“…In 2014, a community-based study in Cornwall, UK [11], reported a phenomenon where 91% of probable SUDEP patients had increased seizure frequency or seizure deterioration 3-6 months prior to their deaths. Our research team published an article in 2016 on the risk factors for probable SUDEP [12], which concluded that non-seizure-free patients were at an increased risk for SUDEP, especially in the months before their deaths. These results implied that SUDEP patients may have more seizures before their deaths.…”
Section: Introductionmentioning
confidence: 99%